Medieval Authorship and Canonicity in the Digital Age – an Introduction (Interfaces: A Journal of Medieval European Literatures, 2021)
Jeroen Deploige and Jeroen De Gussem introduce Cluster 2 of Interfaces 8, on the topic of Medieval Authorship and Canonicity in the Digital Age.
Keywords: stylometrics; Latin style; literary canon; literary archive; authorship